Impact of workplace based assessment on doctors' education and performance: a systematic review. (24th September 2010) - Miller, Alice; Archer, Julian
Abstract : Objective To investigate the literature for evidence that workplace based assessment affects doctors' education and performance. Design Systematic review. Data sources The primary data sources were the databases Journals@Ovid, Medline, Embase, CINAHL, PsycINFO, and ERIC. Evidence based reviews (Bandolier, Cochrane Library, DARE, HTA Database, and NHS EED) were accessed and searched via the Health Information Resources website. Reference lists of relevant studies and bibliographies of review articles were also searched. Review methods Studies of any design that attempted to evaluate either the educational impact of workplace based assessment, or the effect of workplace based assessment on doctors' performance, were included. Studies were excluded if the sampled population was non-medical or the study was performed with medical students. Review articles, commentaries, and letters were also excluded. The final exclusion criterion was the use of simulated patients or models rather than real life clinical encounters. Results Sixteen studies were included. Fifteen of these were non-comparative descriptive or observational studies; the other was a randomised controlled trial. Study quality was mixed. Eight studies examined multisource feedback with mixed results; most doctors felt that multisource feedback had educational value, although the evidence for practice change was conflicting. Some junior doctors and surgeons displayed little willingness to change in response to multisource feedback, whereas family physicians might be more prepared to initiate change. Performance changes were more likely to occur when feedback was credible and accurate or when coaching was provided to help subjects identify their strengths and weaknesses. Four studies examined the mini-clinical evaluation exercise, one looked at direct observation of procedural skills, and three were concerned with multiple assessment methods: all these studies reported positive results for the educational impact of workplace based assessment tools. However, there was no objective evidence of improved performance with these tools. Conclusions Considering the emphasis placed on workplace based assessment as a method of formative performance assessment, there are few published articles exploring its impact on doctors' education and performance. This review shows that multisource feedback can lead to performance improvement, although individual factors, the context of the feedback, and the presence of facilitation have a profound effect on the response. There is no evidence that alternative workplace based assessment tools (mini-clinical evaluation exercise, direct observation of procedural skills, and case based discussion) lead to improvement in performance, although subjective reports on their educational impact are positive.